Wildflowers of Mammoth Cave National Park - Seymour, Randy, 1942- (Book collections on Project MUSE., 1997)
Not only for use in the Mammoth Cave area, this guide is widely useful in a large area, including much of the states of Arkansas, Illinois, Indiana, Missouri, Ohio, Tennessee, and West Virginia. An in-depth field guide to 400 wildflowers found along the trails and roads within the park. Each wildflower is represented by a brilliant full-color photograph and accompanied by identifying characteristic text that specifies the colors, floral and leaf forms, flowering time, native or introduced status, as well as the plant's folklore and history, its past herbal or medicinal use, and myriad other fa.